2013
DOI: 10.1002/ange.201303757
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Single Crystals: Kinematic Analysis of Photoinduced Crystal Jumping (The Photosalient Effect)

Abstract: Kristalle in Bewegung: Bei Bestrahlung mit Licht springen und hüpfen Kristalle der Cobalt‐Koordinationsverbindung [Co(NH3)5(NO2)]Cl(NO3) und legen dabei Distanzen zurück, die 102‐ bis 105‐Mal größer als sie selbst sind, um die Spannung abzubauen, die sich in ihrem Inneren aufbaut. Die erste quantitative kinematische Analyse dieses Phänomens wird beschrieben. Der beobachtete Effekt könnte für Antriebe im makroskopischen Maßstab genutzt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 39 publications
1
57
0
Order By: Relevance
“…This observation of crystal motility was to become the first documented report of the thermosalient (TS) effect (Hüpf-Effekt)-the propensity of certain crystals to hop and leap when heated over a phase transition 9,10,18,19 . Two polymorphs, yellow form (a) and red form (b), were characterized 17 .…”
mentioning
confidence: 89%
“…This observation of crystal motility was to become the first documented report of the thermosalient (TS) effect (Hüpf-Effekt)-the propensity of certain crystals to hop and leap when heated over a phase transition 9,10,18,19 . Two polymorphs, yellow form (a) and red form (b), were characterized 17 .…”
mentioning
confidence: 89%
“…The ambident reactivity of the nitrite ion was studied in detail by Tishkov et al 10 For instance, the cationic cobalt complex of formula [Co(NH 3 ) 5 NO 2 ]Cl 2 exists as either the yellow-colored nitro isomer ([Co(NH 3 ) 5 NO 2 ]Cl 2 ), where the nitro ligand is bound to Co through nitrogen, or the red-colored nitrito isomer ([Co(NH 3 ) 5 ONO]Cl 2 ), where the nitrito is bound to Co through one of the oxygen atoms [11][12][13][14][15][16] Several research groups have focused their studies on metal linkage compounds due to their potential applications in medicinal therapy, photo-responsive materials, tunable optical materials, and molecular devices. [11][12][13][17][18][19][20][21][22][23][24][25][26] The transformation of the N-bonded nitro isomer to the less stable O-bonded nitrito isomer has already been extensively studied experimentally and the conversion was demonstrated to occur intramolecularly. [13][14][15][16] The nitrito isomers of [Co(NH 3 ) 5 -ONO](NO 3 ) 2 and [Co(NH 3 ) 5 ONO](NO 3 )Cl convert slowly to the respective nitro isomers [Co(NH 3 ) 5 NO 2 ](NO 3 ) 2 and [Co(NH 3 ) 5 -NO 2 ](NO 3 )Cl when placed in a dark room.…”
Section: Introductionmentioning
confidence: 99%
“…This solid-state intramolecular reaction changes the conguration of the [Co(NH 3 ) 5 NO 2 ] 2+ complex cation alone at its site in the lattice, leaving the rest of the lattice unchanged 9 and was reported to be autocatalytic or auto-inhibitory. 24 In contrast to the dark condition, Naumov et al 22,23 reported that the [Co(NH 3 ) 5 -NO 2 ](NO 3 )Cl crystal exhibits a forceful jump when exposed to UV light (referred to as the photo-salient effect). During this photo-isomerization process, [Co(NH 3 ) 5 ONO] 2+ was thought to serve as a local source of strains.…”
Section: Introductionmentioning
confidence: 99%
“…While studying the photoreactivity of the coordination metal complexes [Zn 2 (benzoate) 4 (L) 2 ] ( 1 – 3 ) [L=2F‐4spy (2′‐fluoro‐4‐styrylpyridine) in 1 , 3F‐4spy (3′‐fluoro‐4‐styrylpyridine) in 2 and 4spy (4‐styrylpyridine) in 3 ] we serendipitously noted that when crystals of these materials are exposed to even weak UV light, they pop violently (Movie SV1 and SV2 in the Supporting Information, SI). Although several instances of such actuating behavior of crystals induced by heat4 and light2l,n are known, to the best of our knowledge, crystal motility driven by a [2+2] cycloaddition reaction has not been reported yet. In an attempt to establish a mechanistic link between the macroscopic manifestation of the photosalient effect and its origin at a molecular level, we attempted to capture the kinematic details of this extremely rare phenomenon using a high‐speed camera.…”
mentioning
confidence: 99%
“…Herein we report the first instance of an extremely rare phenomenon, photosalient effect,2a,n where a mechanical response that visually (and to some extent, mechanistically) resembles the popping of popcorn kernels on a hot surface occurs in single crystals in response to a solid state [2+2] cycloaddition reaction 3. The photosalient effect is a sudden and rapid actuation of crystals when they are excited with UV light whereby the crystals are propelled to distances many times their own size 2a.…”
mentioning
confidence: 99%